Polarisation of electric field quench radiation from He+(2S) ions - Nemirovsky, I. B. E.; Freschi, N. F. (Institute of Physics (IOP) Publishing, 1982)
Fil: Nemirovsky, I. B. E. Comisión Nacional de Energía Atómica; Argentina